A prospective study comparing preservation of ilioinguinal nerve with neurectomy in open mesh repair of inguinal hernia - Neogi, Probal; Singh, Santosh Kumar; Manwatkar, Soumitra; Singh, Sunil Kumar; Saxena, Abhishek; Kola, Anish (International Surgery Journal, 2018)
Background: Postoperative pain after open mesh repair of inguinal hernia is an important challenge. Such type of pain sometimes does not respond to medical treatment including non-steroidal anti-inflammatory drugs and opiates. The objective of the present study was to evaluate the effect of preservation or division of the Ilioinguinal nerve on pain and post-operative symptoms, after open mesh repair of inguinal hernia. Methods: All patients undergoing surgery for tension free Lichtenstein mesh repair over a period of 1 year were included. Patients below the age of 18 years and patients with bilateral or recurrent hernias were excluded. Results: In present study of 42 patients, early mean postoperative pain at day 1 was 1.8 on VAS scale in ilioinguinal neurectomised patient compared to 1.5 in nerve preserved group (P=0.1408). Postoperative pain at week 1 was 1.25 in neurectomised patients compared to 1.32 in nerve preserved group (P=0.7161). Late Postoperative pain and chronic groin pain was 0.6 and 0.25 at 1 and 3 months respectively in ilioinguinal neurectomised patients as compared to 1.05 and 0.77 at 1 and 3 months respectively in nerve preserved group (P=0.0184 at 1month and P=0.0335 at 3 months). Conclusions: The difference in postoperative pain at day 1 and at week 1 was not significant and both groups had equal pain. Late postoperative pain (at 1 month) and chronic groin pain (at 3 months) was significantly low in ilioinguinal neurectomised patient compared to nerve preserved group.